Analysis Of E-Commerce and Product Innovation in Improving The Financial Performance of MSME In Binjai City 2025 - Anisa, Anisa; Harahap, Ramadhan; Aulia, Aulia (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study analyzes the influence of e-commerce and product innovation in improving the financial performance of MSMEs in Binjai City in 2025. The research is motivated by a drastic decline in the number of MSMEs in 2024, where several sub-districts experienced a significant decline such as North Binjai from 258 to 59 units and East Binjai from 177 to 35 units. This study uses a quantitative approach with primary data collected through questionnaires distributed to 74 respondents of MSMEs in the culinary sector in Tanah Lapang Merdeka Binjai, who were selected using purposive sampling and the Solvin formula. The independent variables studied are e-commerce (X1) and product innovation (X2), while the dependent variable is the financial performance of MSMEs (Y) which is measured through the dimensions of liquidity, solvency, and profitability. Data analysis used multiple linear regression with SPSS version 26. This study is expected to provide practical recommendations on how MSMEs in Binjai City can optimally utilize e-commerce and product innovation to increase competitiveness, expand markets, and ultimately achieve better and more sustainable financial performance. The research findings are expected to serve as a reference for relevant stakeholders in developing policies and programs that support MSME development in Binjai City.